A social kaleidoscope. Family, kinship and Métis identity in the province of Buenos Aires in the 19th century (Quinto Sol, 2013)
The paper studies patterns of family and kinship in the rural areas of the province of Buenos Aires in the 19th century. It intends to approach to the role of women in the transmission of kinship networks and that of kin as a frame of material and emotional protection in a context of intense male mobility and proliferation of matrifocal households. It also pursues the analysis of the sexual and family ethos prevalent at that time.
Keywords: Family; kinship; Métis; frontier